Editorial cartoon collections: a review of indexing challenges. Issue 3 (3rd March 2020) - Stead, Oliver; Liew, Chern Li
Abstract : Purpose: The difficulty of attributing subject to editorial cartoons for indexing purposes exists both for traditional paper-based cartoon formats and for digitized or born-digital cartoons. This paper presents a selective review of literature on indexing editorial cartoons and the associated challenges. Design/methodology/approach: A gap exists in published research on indexing collections of editorial cartoons for online search and retrieval. This paper presents a review of selected works that specifically address the topic of editorial cartoon indexing within a wider context of research that addresses image indexing, subject analysis and indexing challenges more generally. Works that address the interpretation of cartoons by readers and how readers respond to information communicated by editorial cartoons are also considered. Findings: Cartoon controversies in transnational and multicultural contexts, experienced through the international news media since 2000, have dramatically increased research attention and publications in this area. Profound changes in media publication since the advent of the Internet have had an impact on editorial cartoonists and cartoon publishing. Subject indexing of editorial cartoons remains a challenge. Research limitations/implications: The potential for large indexed cartoon collections to be data-mined for topic modeling for research in the social sciences points to the need for indexers of cartoon collections to improve metadata standards and structures to allow improved access to cartoon metadata for computational analysis. Originality/value: This paper places discussion of the technical challenges facing indexers of editorial cartoons within a broader context of discussions about the nature and future of editorial cartooning in rapidly changing media and publishing environments.